Acupressure has not an analgesic effect in patients with renal colic: a randomized controlled trial - Bolvardi, Ehsan; Zarmehri, Bahram; Mousavi Bazzaz, Seyed Mojtaba; Khorsand Vakilzadeh, Ali; Foroughian, Mahdi; Hoseini Faegh, Hasan; Mehramiz, Neema John (Faculty of Medicine, Trisakti University, 2019)
BackgroundEasing renal colic (RC) pain is of the most important issues in the emergency departments. This study was conducted to investigate the analgesic effects of intravenous paracetamol in comparison to acupressure and intramuscular diclofenac in patients with RC.MethodsThis randomized clinical trial was conducted on 96 eligible patients with RC, visiting the Emergency Department of Imam Reza Hospital of Mashhad, Iran. The participants were selected by consecutive non-random sampling method, and were randomized in three groups, each comprising of 32 participants. The first and second groups received 75 mg intramuscular diclofenac and 1g intravenous paracetamol, respectively. In the third group, three acupressure points were manually stimulated for six minutes. The pain score was measured by Visual Analog Scale for pain at baseline and after 10, 30, and 60 minutes. Collected information analyses by SPSS version 20 and interpreted using descriptive statistics (frequency, percentage) and inferential statistics (chi-square test).ResultsThe mean age was 31.60 ± 7.42 years (range:18-50). The two methods (diclofenac and paracetamol groups) were significantly better in pain reduction compared to acupressure after 10 minutes (p<0.001). Ninety four percent of participants in diclofenac group, 87% of paracetamol group and none of acupressure group were completely satisfied with their treatment method (p<0.001).ConclusionThis study demonstrated that acupressure did not effectively reduces renal colic pain. It seems that contrary to acupressure, intravenous paracetamol is a safe and effective analgesic medicine for patients with RC.